Performance, Timing and Persistence of Actively Managed UK Equity Unit Trusts and OEICs - Popat, Chirag (2012)
This paper investigates the performance, timing and persistence of actively managed UK equity Unit Trusts and OEICs between January 2005 and December 2010. Performance of Unit Trusts and OEICs are measured using the one factor model (Jensen’s alpha) and Carhart’s four factor model. The results show that on average Unit Trusts and OEICs are not significantly beating the market, but a few funds do have significant positive alphas; hence, are outperforming the market. Treynor and Mazuy model and Henriksson and Merton model are used to assess the market timing ability of fund managers, but no evidence of this ability is found in either measure. Persistence in performance is measured over two periods; January 2005 – December 2007 and January 2008 – December 2010. Overall Unit Trust and OEICs do not show evidence of overall persistence in performance over these periods, and there is no evidence of Unit Trusts and OEICs consistently beating the market. However, some evidence of persistence in bottom performing funds is found.